The Clinician's Vaccine Safety Resource Guide Optimizing Prevention of Vaccine-Preventable Diseases Across the Lifespan - Dudley, Matthew Z. (Springer International Publishing, 2018)
This book provides clinicians and their staff with essential information on the vaccines that are recommended and not recommended for their patients, the diseases these vaccines prevent, and a broad range of potential vaccine safety issues that may be brought up by their patients. Each topic, from specific vaccines to safety concerns, is covered succinctly, based upon systematic reviews of the scientific literature, with talking points to be used with patients. The organization of the information makes it easy to reference specific topics and quickly find pertinent information, with the most practical details (such as recommendations and causality conclusions) highlighted at the very beginning of the respective sections. There are also sections outlining the vaccine safety system and evidence-based strategies for how to talk with patients about vaccines. This book aims to improve the efficiency and effectiveness of clinical vaccine discussions with patients, leading to more informed patients and timely vaccination. This is an ideal resource for all clinicians administering vaccines and their healthcare teams. .